81 Zearalenone Affects the Ovarian Proteome During Heat Stress in Prepubertal Gilts. (7th May 2021) - Roach, Crystal M; Mayorga, Edith J; Baumgard, Lance H; Ross, Jason W; Keating, Aileen F
Abstract: Zearalenone (ZEA), an estrogenic mycotoxin, causes hormonal disruption and reproductive dysfunction in pigs. Heat stress (HS) occurs when exogenous and metabolic heat accumulation exceeds heat dissipation; a scenario negatively impacting gilt reproduction. Our objective was to identify differentially abundant ovarian proteins in gilts exposed to HS +/- ZEA. We hypothesized that ZEA exposure would negatively impact the prepubertal gilt ovarian proteome and HS would be additive to ZEA-induced toxicity. Prepubertal gilts (n = 38) were assigned to one of six treatment groups: thermoneutral (TN) ad libitum control (TNCtl; n = 6); TN + ZEA (TNZea; 2 ppm; n = 6); pair-fed (PF) control (PFCtl; n = 6); PF+ ZEA (PFZea; 2 ppm; n = 6); cyclical HS control (HSCtl; n = 7); and HS + ZEA (HSZea; 2 ppm; n = 7). Gilts were subjected to TN (20 ± 1°C) or cyclic HS (35 ± 1°C for 12 h/31.6° for 12 h) conditions for 7 d. Liquid chromatography-mass spectrometry (LC-MS/MS) was performed on ovarian protein homogenates. Exposure to ZEA altered (P < 0.05) abundance of 93 proteins in TN gilts (48 increased and 45 decreased). In PF gilts, ZEA increased 50 and decreased 47 proteins (P < 0.05). During HS, ZEA differentially affected (P < 0.05) 126 proteins: 58 increased and 68 increased. Pathways impacted by either HS or ZEA alone or in combination included cellular stress, metabolic pathways, and estrogenic pathways. Thus, ZEA and HS, either alone or in combination, impact the ovarian proteome in prepubertal gilts in ways that could contribute to seasonal infertility. This project was supported by the Iowa Pork Producers Association.